Morphological Analysis of Anak Krakatau Volcano after 22 December 2018 Eruption using Differential Interferometry Synthetic Aperture Radar (DInSAR) - Mochamad Iqbal; Anjar Dwi Asterina Denhi; Kristianto; Ardy Prayoga (UIR PRESS, 2023)
Anak Krakatau Volcano is an active volcano located in the Krakatau Complex, Sunda Strait, Indonesia. On 22 December 2018, the volcano experienced a major eruption that led to a tsunami that devastated the shores of the islands of Java and Sumatra and killed up to 437 people. The eruption also destroyed the volcano’s body and change its shape drastically and forming a large crater in the southwestern part. After that eruption, the volcano continues to grow up. This research aims to analyze the deformation of the Anak Krakatau Volcano post-2018 eruption by using the differential interferometry SAR method (DInSAR). In order to support the analysis, we additionally compare the DInSAR result with tectonic-volcanic activity. Sentinel 1-A type SLC satellite imagery data from 5 June 2019 to 7 January 2020; consisting of 19 images or 18 pairs as master and slave were used to producing a deformation map. DInSAR result shows the volcano was generally experiencing deflation during the period, ranging from -1.03 to -4.81 cm (-3.01 cm average). However, inflation also occurred ranging from 0 to 5.99 cm, correlating with shallow and deep volcanic activity and followed by eruptions in October 2019 when the highest activities were observed. Furthermore, coherence value should be highly considered along with DInSAR processing, and this research allows that coherence to be acceptable.